Bingo: aleatório ou manipulado? - Souza, Heitor José de (2004)
His study comprises the analysis of the main gabling options available for the Brazilian people emphasizing the 'bingos' (a kind of Casino), which were recently shut down by Federal Government. Sundenly they have opened up again due to a decision from the senators defeating the Federal Government. This situation is the key point for a interesting study and conclusion. The focus is on the changing operation of the 'bingos' afterwards the introduction of the slot machines, video poker and so on. These machines have been attracting more and more people who became adicts. Thus the strategy of the 'bingos' have changed in order to preserve the business. It could be seen along this study that those machines, from which results are not randomic, have sky rocketed the profits of the 'bingos' so that the conventional games were back off.